Exploring patient-reported outcomes following percutaneous coronary intervention: A qualitative study - Ayton, D.; Barker, A.; Peeters, G.; Berkovic, D.; Lefkovits, J.; Brennan, A.; Evans, S.; Zalcberg, J.; Reid, Christopher; Stoelwinder, J.; Mcneil, J. (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 John Wiley & Sons Ltd. Background: Percutaneous coronary intervention (PCI) is a common cardiac procedure used to treat obstructive coronary artery disease. Patient-centred care is a priority in cardiovascular health having been shown to increase patient satisfaction, engagement with rehabilitation activities and reduce anxiety. Evidence indicates that patient-centred care is best achieved by routine collection of patient-reported outcomes (PROs). However, existing patient-reported outcome measures (PROMs) have limited the patient involvement in their development. Aims: To identify and explore outcomes, patients perceive as important following PCI. Methods: A qualitative design was adopted. Eight focus groups and five semi-structured interviews were conducted with 32 patients who had undergone PCI in the previous 6 months. Outcomes were identified and mapped under the U.S. Food and Drug Administration (FDA) patient-reported outcome (PROs) domains of feeling (physical and psychological outcomes), function and evaluation. Inductive and deductive analysis methods were used with open, axial and thematic coding. Results: Consistent with prior studies, patients identified feeling and function outcomes such as reductions in physical and psychological symptoms and the ability to perform usual activities as important. Participants also identified a range of new outcomes, including confidence to return to usual activities and evaluation domains such as adverse effects of medications and the importance of patient communication. Conclusion: The findings of this research should be considered in the design of a cardiac PROM for PCI patients. A PROM which adequately assesses these outcomes can provide clinicians and hospital staff with a foundation in which to address these concerns or symptoms.